Análisis Financiero Aplicado al Comercial Reina del Cisne del Cantón Loja, Periodo 2011-1012 y Propuesta de Mejoramiento. - Chacho Pauta, Amanda Marcela (2016)
The research "FINANCIAL ANALYSIS APPLIED TO QUEEN SWAN COMMERCIAL Loja Canton, PERIOD 2011-2012 AND PROPOSED IMPROVEMENT" was held in order to raise awareness of the economic and financial position of the commercial for proper decision-making, which the application of vertical and horizontal analysis was necessary financial reasons and based on the results propose alternatives for improvement. To carry out the proposed topic, it was necessary to consider specific objectives to solve the main problems plaguing the company, among them are: Perform vertical analysis of the years 2011 and 2012 which identified the economic and financial structure of the company Commercial Reina del Cisne which for 2011 was formed mainly with current assets and with respect to the capital structure was financed more with that own borrowings; and in 2012 the funding indicates a structure in equal proportion of both liabilities and equity; The economic situation in the two years 2011 showed a high expenditure of costs and expenses significantly affecting the usefulness of trade and therefore to growth. Upon horizontal analysis increases and decreases were identified in regard to the statement of financial position assets and liabilities increased while equity decreased which is unfavorable because it prevents its capitalization. In the state of economic situation income and expenses 6 they rose, the latter were mainly due to the growth of cost of sales and administrative expenses; what is not right job it does not allow the maximization of profits. The application of financial ratios showed that the company has an adequate level of liquidity, turnover accounts receivable, inventory, and paying suppliers is handled okay, enough revenue is generated to cover their expenditures but the latter are directly affecting high utility, has a debt ratio of 100% with short-term liabilities; which involves high risks of debt. Finally we conclude that the trade should consider better manage its working capital, trying to maintain a structure of healthy capital so that it does not fully commit its assets to finance their fixed assets by long-term debt due to the fixed assets usually have high costs and it is not advisable to borrow short term, promote increased sales volume through marketing policies and reduce costs and expenses so that the business is profitable; This will ensure that the business will unfold efficiently obtaining financial equilibrium in the market.